2022
DOI: 10.7759/cureus.32784
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine in the General Public of Western Saudi Arabia: A Cross-Sectional Survey

Abstract: Background: Complementary and alternative medicine (CAM) has been continuously used worldwide. Various cultures have used this path of healing, and to our date, people are still using it and some even prefer it to modern medicine. Thus, this study aims to analyze awareness, self-use, perceptions, beliefs, and attitudes toward CAM in the general public of Jeddah, Saudi Arabia.Methods: A descriptive observational cross-sectional study was conducted in the public places of Jeddah. Data were collected from 784 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that the use of CAM was more common among people with higher educational levels ( Grundmann, 2014 ). Contrary to that, a study conducted in KSA revealed that participants with low levels of education were more likely to use CAM than those with higher education levels (Syed Faisal Zaidi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the use of CAM was more common among people with higher educational levels ( Grundmann, 2014 ). Contrary to that, a study conducted in KSA revealed that participants with low levels of education were more likely to use CAM than those with higher education levels (Syed Faisal Zaidi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%